Preparation and Characterization of Copper Nanocomposite Catalysts and its Activity for Adsorption of Lead from Aqueous Solution - Saed, Usama Akram; Ali, Israa Shakir M.; Abdulkader, Huda Dhiaa (Al-Nahrain Journal for Engineering Sciences, 2017)
The efficiency of adsorption using copper nanocomposite catalysts for the removal of lead ions from aqueous solution was studied. Nano copper and its nanocomposition were prepared in laboratory in very accurate conditions. After preparing samples, the samples were analyzed using XRD and SEM and that shows very good morphology of catalytic performance and has nano sized of crystalline shape. In order to study the efficiency of these catalysts, all samples were tested using adsorption process. The preparing samples show very good efficiency for lead removing from aqueous solution, and reach maximum removal efficiency 96% for 0.05g of adsorbents at pH 10, otherwise increasing or decreasing the pH would give undesirable results for all samples. Langmuir isotherm fitted better than Freundlich isotherm for adsorption of lead.